10th Anniversary of Axioms: Logic - Castillo, Oscar (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
We are honored to announce this reprint, containing contributions from the top experts in the field of logic and fuzzy logic. In total, this reprint consists of 10 papers that were selected from more than 20 submissions. The 10 papers comprising the reprint are the product of re-known experts in fuzzy logic from all over the world, such as Canada, Poland, China, Slovakia, Lithuania, Turkey, Pakistan, Germany, Serbia, Portugal, Taiwan, Norway, India, Saudi Arabia, Thailand, and Mexico. We expect that the papers comprising the Special Issue will contribute to an advancement in the state of the art in the fields of logic and also fuzzy logic.